A comprehensive review on selected graphene synthesis methods: from electrochemical exfoliation through rapid thermal annealing towards biomass pyrolysis. Issue 21 (21st May 2021) - Prekodravac, Jovana R.; Kepić, Dejan P.; Colmenares, Juan Carlos; Giannakoudakis, Dimitrios A; Jovanović, Svetlana P.
Abstract : A comprehensive overview of selected synthetic methods for graphene and graphene based nanomaterials production with the emphasis on the reaction conditions, the quality of obtained graphene nanomaterials and a variety of potential applications. Abstract : The progressive development of technology and industry in the new millennium emergently requires finding a balance between economic progress and new smart materials. Graphene as a carbon allotrope since the discovery has attracted enormous attention due to several extraordinary properties that originate from its physical and chemical assets. However, the most important obstacle in graphene assembly still is the production of high-quality graphene on a large scale using cost-effective methods. The presented review article aims to give information on a turning point in graphene synthesis, with reference to a detailed analysis of electrochemical exfoliation, rapid thermal annealing and biomass pyrolysis. Selected methods for graphene and graphene-based nanomaterials production were not covered in the literature to their maximum potential, from our point of view. Through an overview of the selected synthesis methods, we explored their prospects and limitations regarding precursor type and reaction conditions. Furthermore, through several important characterization techniques for graphene, we reveal the details of the properties of graphene and graphene-based nanomaterials obtained through selected methods. Finally, a particular potential application depending on nanomaterial properties obtained through selected methods was pointed out.